ELECTRODE FOR FUEL CELLS CONTAINING Pt-Ni COMPOSITE PARTICLES AND ITS MANUFACTURING METHOD
Patent Information
- Application Number
- KR1020250024188
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2026-09-02
Smart Images

Figure PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to an electrode for a fuel cell and a method for manufacturing the same, and more specifically, to an electrode for a fuel cell comprising Pt-Ni composite particles and a method for manufacturing the same. Background Technology
[0002] Polymer Electrolyte Membrane Fuel Cells (PEMFCs) are fuel cells that utilize a polymer membrane with hydrogen ion exchange properties as an electrolyte. They are environmentally friendly and are attracting attention as a next-generation energy source for power generation, transportation, and portable devices. As an electrochemical device designed to generate electricity, hydrogen oxidation occurs at the anode, separating it into electrons and hydrogen ions. The separated electrons reach the cathode via an external wire, while the hydrogen ions reach the anode through the electrolyte membrane, forming a triple-phase boundary. There, protons, electrons, oxygen, and a catalyst meet to trigger a reduction reaction, generating water and electricity. While platinum (Pt) catalysts are used to facilitate these electrochemical catalytic reactions (oxidation and reduction), the high cost resulting from the scarcity of the precious metal platinum is one of the factors hindering the commercialization of PEMFCs. Accordingly, the U.S. Department of Energy (2025 DOE) recommends low-dose platinum loading (oxidation, reduction anode: 0.100 mgPGM / cm²) 2 ) was proposed as a goal, and research on low-capacity platinum for the commercialization of polymer electrolyte membrane fuel cells remains challenging.
[0003] Currently, Pt / C catalysts in which platinum is supported on a carbon support are commercially available to increase the specific surface area of platinum. Micell and polyol methods are used to produce Pt / C catalysts, but these wet processes use chemical organic solvents, which have harmful effects on the environment during the manufacturing process, and the complex manufacturing process increases the unit cost of the catalyst.
[0004] In addition, catalyst layers made with commercial Pt / C catalysts have a thickness of approximately 5-10 μm. Such thick catalyst layers form a concentration gradient of reactants (hydrogen ions, oxygen) and generate mass transfer resistance, which causes the problem that not all platinum in the catalyst layer participates in the electrochemical reaction and is wasted.
[0005] Accordingly, there is a need for catalyst technology that can improve the performance of polymer electrolyte membrane fuel cells at a low cost. The problem to be solved
[0006] The present invention was devised to solve the aforementioned conventional problems and aims to reduce the amount of precious metal Pt used and to provide a fuel cell electrode having excellent catalytic performance and a method for manufacturing the same. means of solving the problem
[0007] The present invention discloses an electrode for a fuel cell, comprising, as a means to achieve the above-described objective: a carbon support; and a catalyst layer comprising Pt-Ni composite particles formed on the surface of the carbon support.
[0008] Here, the carbon support may be one or more materials selected from the group consisting of carbon nanotubes.
[0009] Here, the carbon support may have inherent structural defects.
[0010] Here, the above Pt-Ni composite particles may be core-shell structured Pt-Ni composite particles or alloy-phase Pt-Ni composite particles.
[0011] Here, the above Pt-Ni composite particles may contain Pt and Ni in an elemental ratio of 1:1 to 6:1.
[0012] Here, the Pt-Ni composite particle with the core-shell structure described above may contain Ni in the core and Pt in the shell.
[0013] Here, the diameter of the above Pt-Ni composite particles may be 4 to 10 nm.
[0014] Here, the Pt loading amount of the electrode is 0.04 to 0.05 mg / cm² 2 It could be.
[0015] In addition, the present invention discloses a method for manufacturing an electrode for a fuel cell, comprising the steps of: preparing a carbon support; and forming a catalyst layer containing Pt-Ni composite particles on the surface of the prepared carbon support, as a means to achieve the above-described objective.
[0016] Here, the step of preparing the carbon support may include: a step of forming a carbon sheet through a carbon source; a step of heat-treating the formed carbon sheet; and a step of acid-treating the heat-treated carbon sheet.
[0017] Here, the carbon source may be one or more substances selected from the group consisting of ethanol, methanol, propanol, acetone, xylene, chloroform, ethyl acetic acid, diethyl ether, polyethylene glycol, ethyl formate, mesitylene, tetrahydrofuran (THF), dimethylformamide (DMF), dichloromethane, hexane, benzene, carbon tetrachloride, and pentane, but is not limited thereto.
[0018] Here, the thickness of the carbon sheet formed above may be 5 to 30 μm.
[0019] Here, the step of forming the carbon sheet can be performed according to the direct spinning method.
[0020] Here, the heat treatment can be performed at a temperature of 450 to 650 ℃.
[0021] Here, the acid treatment can be performed using one or more acids selected from the group consisting of HCl, HNO3, HF, HClO4, H3PO4, HCRO4, and H2SO4.
[0022] Here, the step of forming the catalyst layer can be performed through a co-spurttering process using a Ni target and a Pt target on the surface of the prepared carbon support.
[0023] Here, the sputtering process can be performed for 100 to 500 seconds.
[0024] Here, the step of forming the catalyst layer may involve sputtering the Ni target or the Pt target individually, or sputtering the Ni target and the Pt target simultaneously.
[0025] In addition, the present invention discloses a polymer electrolyte fuel cell comprising, as a means to achieve the above-described objective, an electrode for a fuel cell comprising a carbon support and a catalyst layer comprising Pt-Ni nanoparticles formed on the surface of the carbon support; and a polymer ion exchange membrane. Effects of the invention
[0026] The fuel cell electrode of the present invention can reduce the amount of expensive Pt used, thereby allowing for the expectation of reduced manufacturing costs.
[0027] In addition, the electrode for a fuel cell of the present invention includes Pt-Ni composite particles as a catalyst layer, thereby enabling an improvement in catalyst efficiency due to the alloying effect.
[0028] In addition, the method for manufacturing an electrode for a fuel cell according to the present invention can reduce material costs and waste disposal costs by excluding the use of organic solvents and reducing agents, thereby allowing for the expectation of reduced manufacturing costs. Brief explanation of the drawing
[0029] FIG. 1 is a schematic diagram illustrating the appearance of an electrode for a fuel cell according to the present invention. FIG. 2 is a flowchart illustrating the manufacturing process of an electrode for a fuel cell according to the present invention. FIG. 3 is a schematic diagram illustrating the manufacturing process of an electrode for a fuel cell according to the present invention. Figure 4 is an SEM image of a carbon support manufactured according to one embodiment of the present invention. Figure 5 is a Raman spectrum of a carbon support manufactured according to one embodiment of the present invention. Figure 6 is a surface and cross-sectional SEM image of an electrode for a fuel cell manufactured according to one embodiment of the present invention. FIG. 7 is an EDS elemental mapping image of an electrode for a fuel cell manufactured according to one embodiment of the present invention. FIG. 8 is an SEM image of a fuel cell electrode manufactured according to one embodiment of the present invention. FIG. 9 is an XRD spectrum of a fuel cell electrode manufactured according to one embodiment of the present invention. FIG. 10 is an XPS spectrum of an electrode for a fuel cell manufactured according to one embodiment of the present invention. FIG. 11 is a graph showing the UPS spectrum and Fermi level of an electrode for a fuel cell manufactured according to one embodiment of the present invention. FIG. 12 is a schematic diagram of an electrode for a fuel cell according to one embodiment of the present invention and a TEM image of an electrode for a fuel cell manufactured according to one embodiment. Figure 13 is the result of an EDS line mapping analysis of an electrode for a fuel cell manufactured according to one embodiment of the present invention. FIG. 14 is a polarization curve of an electrode for a fuel cell manufactured according to one embodiment of the present invention. FIG. 15 is a CV curve of an electrode for a fuel cell manufactured according to one embodiment of the present invention. FIG. 16 is a graph comparing the power density according to the electrode area and Pt content of an electrode for a fuel cell manufactured according to one embodiment of the present invention. FIG. 17 is an EIS curve of a fuel cell electrode manufactured according to one embodiment of the present invention. Specific details for implementing the invention
[0030] The present invention is capable of various modifications and may have various embodiments, and specific embodiments are illustrated in the drawings and described in detail in the detailed description. However, this is not intended to limit the invention to specific embodiments, and it should be understood that the invention includes all modifications, equivalents, and substitutions that fall within the spirit and scope of the invention.
[0031] Throughout this specification, when a part is described as "comprising" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.
[0032] As used herein, terms of degree such as “about,” “substantially,” etc., are used to mean at or near the stated value when inherent manufacturing material tolerances are presented in the said sense, and are used to prevent unscrupulous infringers from unfairly exploiting the disclosed content in which precise or absolute values are mentioned to aid in understanding the invention. Furthermore, throughout this specification, “a step of” or “a step of” does not mean “a step for”.
[0033] Since a person skilled in the art can make various applications through the gist of the present invention, the scope of the rights of the present invention is not limited to the following embodiments. The scope of the rights of the present invention extends to parts that are obvious to a person skilled in the art who can easily substitute or modify using prior art based on the matters described in the specific claims.
[0034] The present invention will be described in more detail below with reference to the attached drawings, where necessary.
[0036] Electrode for fuel cell
[0037] The present invention discloses a fuel cell electrode comprising Pt-Ni composite particles in a catalyst layer as a means to achieve the above-mentioned objective.
[0038] FIG. 1 is a schematic diagram illustrating the appearance of an electrode for a fuel cell according to the present invention. Referring to FIG. 1, the electrode for a fuel cell according to the present invention is described as follows. The electrode for a fuel cell according to the present invention may include a carbon support having inherent defects; and a catalyst layer comprising Pt-Ni composite particles formed on the carbon support.
[0039] Here, the carbon support may be one or more materials selected from the group consisting of carbon black, acetylene black, carbon nanotubes, graphite, graphene, graphite nanofibers, and fullerene. In the present invention, the most preferred carbon support may be carbon nanotubes, but is not limited thereto. Carbon nanotubes are useful as a support for sputtering because they have excellent specific surface area, mechanical strength, electrical conductivity, and chemical stability.
[0040] Here, the carbon support may have inherent structural defects. The defects in the carbon support may be imparted through a separate process. For example, defects in the carbon support may be imparted through heat treatment and / or acid treatment processes. The method of imparting defects to the carbon support will be explained in more detail in the section <Method for Manufacturing an Electrode for a Fuel Cell> described later.
[0041] Here, the Pt-Ni composite particles may be core-shell structured Pt-Ni composite particles. More specifically, the core-shell structured Pt-Ni composite particles may refer to a structure containing Ni in the core and Pt in the shell. Additionally, the core-shell structured Pt-Ni composite particles may be formed with a concentration gradient in which the amount of Pt loading gradually increases as it moves from the core to the shell through a cavity sputtering process.
[0042] In addition, the above Pt-Ni composite particles may be alloy-phase Pt-Ni composite particles. In other words, the above Pt-Ni composite particles may be particles in which Pt and Ni form an alloy.
[0043] In the present invention, since Pt-Ni composite particles are included in the catalyst layer, the amount of platinum, a precious metal, used can be reduced, which is not only economical but also allows for the expectation of improved catalyst efficiency due to the alloying effect.
[0044] Here, it is preferable that the above Pt-Ni composite particles contain Pt and Ni in an elemental ratio of 1:1 to 6:1, and it is more preferable that Pt and Ni be included in an elemental ratio of 3:1. If the above Pt is included in a range lower than the elemental ratio described above, a problem may arise in that it is difficult to achieve the desired catalytic efficiency. In addition, if the above Pt is included in a range higher than the elemental ratio described above, a problem may arise in that the amount of expensive Pt used increases, leading to an increase in process costs.
[0045] Here, it is preferable that the diameter of the Pt-Ni composite particles be 4 to 10 nm. If the diameter of the Pt-Ni composite particles is less than 4 nm, it is not economical because excessive processing is required to make the particle diameter 4 nm. In addition, if the diameter exceeds 10 nm, a decrease in the active area due to the increase in particle size may occur, which may result in a problem of reduced catalyst efficiency. Accordingly, it is preferable that the diameter of the Pt-Ni composite particles be 4 to 10 nm.
[0046] The Pt loading amount of the above electrode is 0.04 to 0.05 mg / cm² 2 This is desirable. If the Pt loading amount of the electrode is included in a range lower than the aforementioned range, a problem may arise where it is difficult to achieve the desired catalyst efficiency. Furthermore, if the Pt is included in a range higher than the aforementioned range, a problem may arise where the use of expensive Pt increases, leading to higher process costs.
[0048] Method for manufacturing an electrode for a fuel cell
[0049] In addition, the present invention discloses a method for manufacturing an electrode for a fuel cell comprising Pt-Ni composite particles in a catalyst layer as a means to achieve the above-mentioned objective.
[0050] FIG. 2 is a flowchart illustrating the manufacturing process of an electrode for a fuel cell according to the present invention. Referring to FIG. 2, it can be seen that the method for manufacturing an electrode for a fuel cell according to the present invention includes the step of preparing a carbon support; and the step of forming a catalyst layer containing Pt-Ni composite particles on the surface of the prepared carbon support.
[0051] Below, the manufacturing method of the present invention will be described in more detail by subdividing it into each step.
[0052] First, the manufacturing method of the present invention includes the step of preparing a carbon support.
[0053] Here, the step of preparing the carbon support may include: a step of forming a carbon sheet through a carbon source; a step of heat-treating the formed carbon sheet; and a step of acid-treating the heat-treated carbon sheet.
[0054] Here, the step of forming the carbon sheet can be performed according to the direct spinning method. More specifically, a carbon sheet precursor solution can be prepared, and a carbon sheet can be finally formed through a direct spinning process. The carbon sheet precursor solution may be, for example, a mixture of a catalyst precursor, a catalyst activator, and a carbon source.
[0055] Here, the carbon source may be one or more substances selected from the group consisting of ethanol, methanol, propanol, acetone, xylene, chloroform, ethyl acetic acid, diethyl ether, polyethylene glycol, ethyl formate, mesitylene, tetrahydrofuran (THF), dimethylformamide (DMF), dichloromethane, hexane, benzene, carbon tetrachloride, and pentane, but is not limited thereto.
[0056] The catalyst precursor may be ferrocene, etc., and the catalyst activator may be thiophene, etc., but is not limited thereto. At this time, the catalyst precursor, the catalyst activator, and the carbon source may be mixed in a weight ratio of 1 : (3 to 5) : (75 to 85), but is not limited thereto.
[0057] Here, the thickness of the carbon sheet formed above is preferably 5 to 30 μm. A more preferable thickness of the carbon sheet may be 10 to 20 μm, and most preferably 13 to 17 μm. If the sheet is manufactured with a thickness thinner than the above range, the effect of improving battery performance may be insufficient, and if it is manufactured with a thickness thicker than the above range, problems such as reduced gas diffusion and permeability may occur.
[0058] The carbon sheet may be in a porous form having micropores, and the average particle size of the pores may be 30 to 40 nm, but is not limited thereto. By making the size of the pores within the range described above, crystals of Pt-Ni composite particles can be grown densely only on the carbon sheet.
[0059] Here, the step of heat-treating the formed carbon sheet is preferably performed at a temperature of 450 to 650 ℃. By heat-treating the carbon sheet within the temperature range described above, the amorphous carbon remaining in the carbon sheet can be removed.
[0060] Here, the step of acid-treating the heat-treated carbon sheet may be performed using one or more acids selected from the group consisting of HCl, HNO3, HF, HClO4, H3PO4, HCRO4, and H2SO4, but is not limited thereto. In the present invention, the most preferred acid for the acid treatment may be HCl.
[0061] The acid treatment step described above may involve immersing the prepared carbon sheet in a solution containing the acid described above for 30 to 1 hour.
[0062] Next, the manufacturing method of the present invention includes the step of forming a catalyst layer containing Pt-Ni composite particles on the surface of the prepared carbon support.
[0063] Here, the step of forming the catalyst layer can be performed on the surface of the prepared carbon support through a co-spurttering process using a Ni target and a Pt target. Sputtering is a process utilized for depositing thin films, and the shape of the porous thin film formed can be easily controlled through the sputtering process conditions. Furthermore, the co-spurttering process is expected to have the effect of depositing Pt-Ni composite particles on the carbon sheet through a simple process of controlling the shutters of multiple target metals.
[0064] Here, it is preferable that the sputtering process be performed for 100 to 500 seconds. If the sputtering process is performed for less than 100 seconds, it is difficult to form the desired amount of catalyst particles (Pt-Ni composite particles), and if it is performed for more than 500 seconds, a problem may arise in which the active area decreases as the size of the catalyst particles and the thickness of the catalyst layer increase.
[0065] At this time, the step of forming the catalyst layer may involve sputtering the Ni target or the Pt target individually, or sputtering the Ni target and the Pt target simultaneously. More specifically, the deposition of Pt-Ni composite particles on an alloy can be achieved by simultaneously opening the shutters of the Ni target and the Pt target for a certain period of time, and the deposition of Pt-Ni composite particles with a core-shell structure can be achieved by first opening the shutter of the metal target (e.g., Ni) included in the core, and then opening the shutter of the metal target (e.g., Pt) included in the shell. In addition, a uniform concentration gradient of the catalyst metal from the core to the shell can be achieved by performing the steps in the order of opening the shutter of the metal (Ni) target included in the core → simultaneous opening of the shutters of multiple metal targets (Pt & Ni) → opening the shutter of the metal (Pt) target included in the shell.
[0066] Although there is no limitation on the opening time of each of the above shutters, in the present invention, for core-shell structured Pt-Ni composite particles, it is preferable to sputter in the order of a. Ni 60 seconds → b. PtNi 180 seconds → c. Pt 180 seconds, and for alloyed Pt-Ni composite particles, it is preferable to sputter in the order of a. Ni 60 seconds → b. PtNi 360 seconds.
[0067] FIG. 3 is a schematic diagram illustrating the manufacturing process of an electrode for a fuel cell according to the present invention. Referring to FIG. 3, the manufacturing process according to one embodiment of the present invention will be described in more detail as follows. A carbon sheet (specifically, a CNT sheet) can be synthesized through a direct spinning process using chemical vapor deposition. During synthesis, the CNT sheet can be synthesized by controlling the amount of acetone, which is the carbon source, the synthesis time, and the CNT fiber collection speed of the roller. At this time, the thickness of the synthesized CNT sheet may be 5 to 30 μm. Subsequently, the CNT sheet may be acid-treated to introduce defects. As defects are introduced into the CNT sheet, impurities remaining in the CNT sheet can be removed, and furthermore, the bonding strength with deposited particles such as Pt, Ni, etc., can be strengthened. The acid-treated CNT sheet can be placed in a high-vacuum sputtering chamber to deposit Pt or Ni. The deposition conditions are, for example, 10 -6After reaching a pressure of mTorr or less, an Ar flow rate of 20 sccm can be flowed into a high vacuum chamber to perform deposition at an operating pressure of 50 mTorr, but this is not limited thereto. Subsequently, power of 30 W and 40 W from a DC power source can be applied to the Pt and Ni targets, respectively. The deposition amount of each metal can be controlled through shutter control for each target. For example, if only the shutter of the Pt target is opened for a certain period of time, particles with an elemental ratio of 100% Pt can be deposited on the CNT sheet. In addition, for the deposition of core-shell structured Pt-Ni composite particles, the process can be performed in the order of 1) opening the Ni target shutter, 2) simultaneously opening the Ni target and Pt target shutters, and 3) opening the Pt target shutter. In addition, for the deposition of Pt-Ni composite particles on an alloy, the process can be performed in the order of 1) opening the Ni target shutter, and 2) simultaneously opening the Ni target and Pt target shutters. There is no limit to the deposition time for each target, but for core-shell structured Pt-Ni composite particles, the process can be performed in the order of Ni 60 seconds → PtNi 180 seconds → Pt 180 seconds, and for alloy-phase Pt-Ni composite particles, the process can be performed in the order of Ni 60 seconds → PtNi 360 seconds. At this time, the Pt loading of the sample may be 0.04 to 0.05 mg / cm².
[0069] Fuel cell
[0070] In addition, the present invention discloses a polymer electrolyte fuel cell as a means to achieve the above-mentioned purpose.
[0071] The polymer electrolyte fuel cell of the present invention may include an electrode for a fuel cell comprising a carbon support and a catalyst layer comprising Pt-Ni nanoparticles formed on the surface of the carbon support; and a polymer ion exchange membrane.
[0072] The electrode for a fuel cell of the present invention described above can be used as a reduction electrode, and the fuel cell of the present invention may further include an oxidation electrode in addition to the electrode for a fuel cell described above.
[0073] The oxidation electrode may include a catalyst layer, a gas diffusion layer (GDL), or a microporous layer (MPL).
[0074] The above polymer ion exchange membrane can be used without limitation as long as it is a known polymer ion exchange membrane used in conventional polymer ion exchange membrane fuel cells.
[0075] Hereinafter, the claims of this specification will be explained in more detail with reference to the attached drawings and embodiments. However, as the drawings and embodiments presented in this specification may be modified in various ways by a person skilled in the art and may take various forms, the details described in this invention should not be limited to a specific disclosed form, but should be understood to include all equivalents and substitutions included within the spirit and technical scope of this invention. Furthermore, the attached drawings are presented to help a person skilled in the art understand the invention more accurately and may be depicted in an exaggerated or reduced size compared to the actual size.
[0077] {Examples and Evaluation}
[0078] <Example>
[0079] Example 1
[0080] CNT sheets were synthesized through a direct spinning process using chemical vapor deposition. The precursor solution was prepared by mixing a carbon source acetone, a catalyst precursor ferrocene, and an promoter thiophene. The mixing ratios were composed of 99.0 wt% acetone, 0.2 wt% ferrocene, and 0.8 wt% thiophene.
[0081] The prepared precursor solution was injected into a vertical CVD reactor preheated to 1450 °C with a carrier gas (hydrogen, 99.99%) at flow rates of 0.6 and 2200 sccm, respectively. The grown CNTs were collected in the form of sheets via rollers, with a thickness of 15 μm.
[0082] The prepared CNT sheets underwent a process to remove amorphous carbon by heat treatment in an air atmosphere at 550 °C for 30 minutes (heating rate: 10 °C / min). The heat-treated CNT sheets were then acid-treated with 11.32 M HCl in an oil bath at 80 °C for 30 minutes to remove remaining iron catalyst seeds and impart defects to the CNT fibers. Subsequently, the sheets were washed with distilled water and ethanol and dried in a drying oven for 12 hours to obtain the final purified CNT sheets.
[0083] Next, Pt targets and Ni targets were deposited on the CNT sheet using magnetron sputtering. The sputtering chamber was 10 -6 After reaching a vacuum of mTorr, sputtering was performed at an operating pressure of 50 mTorr by flowing an Ar flow rate of 20 sccm for deposition. The target-substrate distance was 121 mm, and 5 cm 2 To deposit the reaction region, the sample was masked and deposited.
[0084] 30 W and 40 W were applied to the Pt target and Ni target, respectively, from a DC power source. The deposition amount of each metal was controlled as follows through shutter control of each target.
[0085] a. Ni 60 sec → b. PtNi 180 sec → c. Pt 180 sec
[0086] Subsequently, an electrode for a fuel cell was manufactured by removing residual gas inside the sample through a high vacuum state (hereinafter referred to as "Example 1").
[0087] At this time, the Pt loading amount is 0.04 mg / cm² 2It was.
[0089] Example 2
[0090] An electrode for a fuel cell was manufactured in the same manner as in Example 1, except that in the sputtering process of Example 1 above, the shutters of the Pt target and the Ni target were controlled as follows (hereinafter referred to as "Example 2").
[0091] a. Ni 60 seconds → b. PtNi 360 seconds
[0092] At this time, the Pt loading amount is 0.04 mg / cm² 2 It was.
[0094] Comparative Example 1
[0095] An electrode for a fuel cell was manufactured in the same manner as in Example 1, except that in the sputtering process of Example 1 above, the shutter of the Pt target was controlled as follows without a Ni target (hereinafter referred to as "Comparative Example 1").
[0096] a. Pt 420 seconds
[0097] At this time, the Pt loading amount is 0.05 mg / cm² 2 It was.
[0099] Comparative Example 2
[0100] An electrode for a fuel cell was manufactured in the same manner as in Example 1, except that in the sputtering process of Example 1 above, the shutter of the Ni target was controlled as follows without a Pt target (hereinafter referred to as "Comparative Example 2").
[0101] a. Ni 60 seconds
[0103] Comparative Example 3
[0104] An electrode for a fuel cell was manufactured in the same manner as in Example 1, except that in the sputtering process of Example 1 above, the shutters of the Pt target and the Ni target were controlled as follows (hereinafter referred to as "Comparative Example 3").
[0105] a. Ni 60 seconds → b. PtNi 180 seconds
[0107] Comparative Example 4
[0108] Commercially available Pt / C (platinum on carbon) was used as the electrode for a fuel cell (hereinafter referred to as "Comparative Example 4").
[0110] Each of the above-prepared examples and comparative examples was physically attached to the reduction electrode surface of a Nafion membrane, and the catalyst ink described below was sprayed onto the oxidation electrode surface to fabricate an MEA. At this time, the active surface area of the oxidation electrode was 5 cm² 2 and the oxidation electrode Pt loading is 0.05 mg / cm² 2 It was.
[0111] The above catalyst ink was prepared by mixing a commercial Pt / C catalyst, deionized water, Nafion® solution, and isopropyl alcohol.
[0113] For convenience of explanation, the electrodes for fuel cells manufactured according to each of the above examples and comparative examples; and the fuel cells manufactured including the electrodes for fuel cells; are all referred to as examples and comparative examples.
[0115] <Evaluation>
[0116] FIG. 4 is an SEM image of a carbon support manufactured according to one embodiment of the present invention. More specifically, FIG. 4a is an SEM image of the surface of a carbon support before acid treatment, and FIG. 4b is an SEM image of the surface of a carbon support after acid treatment.
[0117] Referring to FIG. 4, it can be seen that impurities such as residual iron catalyst seeds are removed from the carbon support of the present invention as acid treatment is performed. This can also be confirmed through carbon crystallinity.
[0118] Figure 5 is a Raman spectrum of a carbon support prepared according to an embodiment of the present invention. In Raman analysis, the G band indicates the graphitization of carbon, and the D band shows the degree of disorder and structural defects within the carbon lattice. The ratio of the G band peak intensity to the D band peak intensity (I G / I D ) is used as an indicator for evaluating the crystallinity of CNTs.
[0119] Referring to Fig. 5, the I of the acid-treated CNT and the CNT before acid treatment G / I D I of acid-treated CNTs is 5.57 and 8.61, respectively. G / I D It can be confirmed that this appears relatively low. As mentioned above, this means that the defect ratio in acid-treated CNTs is high. The defects in acid-treated CNTs provide additional dangling bonds, which can provide enhanced bond strength during metal deposition.
[0120] FIG. 6 is a surface and cross-sectional SEM image of an electrode for a fuel cell manufactured according to one embodiment of the present invention. Specifically, FIG. 22 is a surface SEM image of Comparative Example 1, FIG. 6b is a surface SEM image of Example 1, FIG. 6c is a surface SEM image of Example 2, FIG. 6d is a cross-sectional SEM image of Comparative Example 1, FIG. 6e is a cross-sectional SEM image of Example 1, and FIG. 6f is a cross-sectional SEM image of Example 2.
[0121] By adjusting the total sputtering deposition time of the catalyst for each sample to 420 seconds to uniformly control the amount of catalyst deposited, the effect on the pore size and mass transfer characteristics of the CNT sheet was minimized. Referring to Fig. 6, it can be confirmed that each sample of the comparative example and the example has a similar amount of catalyst deposited on the CNT strand.
[0122] FIG. 7 is an EDS elemental mapping image of an electrode for a fuel cell manufactured according to one embodiment of the present invention. More specifically, FIG. 7a is an EDS elemental mapping image of Comparative Example 1, FIG. 7b is an EDS elemental mapping image of Example 1, and FIG. 7c is an EDS elemental mapping image of Example 2.
[0123] In the case of an electrode for a fuel cell, since electrochemical reactions occur only at the interface between the electrode and the electrolyte, a catalyst must be deposited at a high concentration on the surface of the CNT sheet to ensure high catalyst utilization efficiency. Referring to FIG. 7, it can be seen that the catalysts Pt and Ni have a high distribution on the surface of the CNT sheet by using the sputtering method of the present invention.
[0124] FIG. 8 is an SEM image of an electrode for a fuel cell manufactured according to one embodiment of the present invention. More specifically, FIG. 8a is an SEM image of Comparative Example 1, FIG. 8b is an SEM image of Example 2, and FIG. 8c is an SEM image of Example 1.
[0125] The size of the catalyst particles deposited in each comparative example and example was analyzed through the SEM image of Fig. 8. Referring to Fig. 8, it can be seen that in the case of Comparative Example 1, catalyst particles (Pt particles) with an average size of about 6.41 nm are formed, in the case of Example 2, catalyst particles (Pt-Ni composite particles on an alloy) with an average size of about 6.93 nm are formed, and in the case of Example 1, catalyst particles (Pt-Ni composite particles with a core-shell structure) with an average size of about 5.84 nm are formed.
[0126] FIG. 9 is an XRD spectrum of an electrode for a fuel cell manufactured according to one embodiment of the present invention. More specifically, FIG. 9a compares the XRD spectra of Examples 1 to 2 and Comparative Examples 1 to 4, FIG. 9b compares the XRD spectra of Examples 1 to 2 and Comparative Example 1 and Comparative Example 4, and FIG. 9c compares the lattice constants of Examples 1 to 2 and Comparative Example 1 and Comparative Example 4.
[0127] Referring to Fig. 9, the results of the nanostructure analysis of the composite particles via XRD confirmed that the grain sizes of Comparative Example 1, Example 2, and Example 1 were 6.30, 6.07, and 4.55 nm, respectively. Among these, the particle size of Example 2 was the largest, which can be inferred to be due to the influence of the deposition angle caused by co-sputtering of two metal targets, Pt and Ni. For Comparative Example 1, Example 2, and Example 1, XRD was performed together with CNT for comparison, Comparative Example 2 (Ni 60s deposition), Comparative Example 3 (Ni 60s → PtNi 180s deposition), and Comparative Example 4. When comparing CNT, Comparative Example 2, and Comparative Example 3, it can be confirmed that the Ni core was well deposited through the Ni (111) and Ni (200) peaks identified in Comparative Example 2. Comparing Comparative Example 3 with Example 1, it can be confirmed that Pt was well deposited on the surface of the catalyst through the relatively reduced peak angle of Pt (111) in Example 1. The peak angles of Pt (111) for Comparative Example 1, Example 2, and Example 1 are 39.70, 40.90, and 40.24°, respectively, and the Pt (111) lattice constants calculated from this are 3.93, 3.82, and 3.88 Å, respectively. As Ni is alloyed with Pt, the Pt (111) peak angle increases and shows a shifting phenomenon, and it can be confirmed that the resulting decrease in lattice constant behavior is consistent with Vegard's law. This implies that the catalyst of Example 2, fabricated by sputtering, exhibits alloy characteristics.
[0128] Figure 10 is an XPS spectrum of a fuel cell electrode manufactured according to one embodiment of the present invention. More specifically, Figure 10a is an XPS spectrum for Pt, and Figure 10b is an XPS spectrum for Ni. XPS analysis was performed to analyze the binding energy and chemical composition changes caused by the formation of metallic bonds in composite particles.
[0129] Referring to FIG. 10, the binding energies of Pt 4f in Comparative Example 1, Example 1, and Example 2 are 74.55, 74.41, and 74.41 eV, respectively, and it can be seen that the binding energy of Pt 4f in Example 2 is 0.135 eV lower than that of Comparative Example 1. This result is attributed to the increase in Pt electron density due to metallic bonding during alloying caused by the difference in electronegativity between Pt (2.28) and Ni (1.91), and from this, it can be confirmed that the composite particles produced by co-sputtering formed a metallic alloy well.
[0130] FIG. 11 is a graph showing the UPS spectrum and Fermi level of an electrode for a fuel cell manufactured according to one embodiment of the present invention. More specifically, FIG. 11a is the UPS spectrum of Example 1, Example 2 and Comparative Example 1, and FIG. 11b is a graph showing the Fermi level of Example 1, Example 2 and Comparative Example 1.
[0131] Referring to Fig. 11, the cutoff voltages obtained from UPS analysis were 16.62, 16.65, and 16.47 eV for Comparative Example 1, Example 1, and Example 2, respectively, and the work functions calculated from this were 4.6, 4.57, and 4.75 eV, respectively. Qualitative comparison of the Fermi level and d-band energy levels of each catalyst based on the work functions revealed that the d-band energy level of Example 2 was lower than that of Comparative Example 1. As the d-band center shifts downward, the oxygen adsorption energy decreases, which can enhance the oxygen reduction reaction of the polymer electrolyte membrane fuel cell. Furthermore, the decrease in the Pt 4f binding energy of the alloy catalyst confirmed an increase in Pt electron density through the formation of metallic bonds; from this, it was confirmed that the work function increased, causing the d-band center to shift downward. Therefore, it can be inferred that the lowered oxygen adsorption energy of the sputtered alloy catalyst increases catalytic activity.
[0132] FIG. 12 is a schematic diagram of a fuel cell electrode according to one embodiment of the present invention and a TEM image of a fuel cell electrode manufactured according to one embodiment. More specifically, FIG. 12a is an atomic-level schematic diagram of a fuel cell electrode of the present invention, and FIG. 12b is a TEM image of a fuel cell electrode manufactured according to Example 1. The nanostructure deposition shape and structural components of the composite particles were confirmed from high-resolution FE-TEM.
[0133] Referring to Fig. 12, as shown in the schematic diagram, the shape of catalyst particles deposited on the surface of the CNT support layer in an actual manufactured fuel cell electrode can be observed.
[0134] FIG. 13 is the result of EDS line mapping analysis of an electrode for a fuel cell manufactured according to one embodiment of the present invention. More specifically, FIG. 13a and b show the result of EDS line mapping analysis of an electrode manufactured according to Example 2, and FIG. 13c and d show the result of EDS line mapping analysis of an electrode manufactured according to Example 1.
[0135] Referring to Fig. 13, it can be seen that in Example 2, Ni and Pt are uniformly distributed, and in Example 1, the Pt composition appears slightly higher on the surface.
[0136] FIG. 14 is a polarization curve of an electrode for a fuel cell manufactured according to one embodiment of the present invention.
[0137] Voltage loss occurs to induce hydrogen oxidation at the fuel cell electrodes and oxygen reduction at the air electrode; this loss is called activation loss and occurs when the current density is low. When operating at a higher current density, the system eventually reaches a value where the voltage drops sharply, indicating that the hydrogen supply rate to the fuel electrode layer has reached a limit. In other words, because the supply rate of hydrogen fuel is slower than the consumption rate of hydrogen by the reaction, the hydrogen oxidation reaction can no longer proceed; this is called concentration loss (or mass transfer loss). Additionally, the loss caused by electrode resistance and the resistance that occurs as charges pass through the electrolyte is called ohmic resistance loss.
[0138] Referring to FIG. 14, the magnitude of the maximum power density is in the order of Example 2, Example 1, Comparative Example 1, and Comparative Example 4, which can be seen to confirm that the fuel cell according to the present invention exhibits excellent performance.
[0139] FIG. 15 is a CV curve of an electrode for a fuel cell manufactured according to one embodiment of the present invention.
[0140] In the curve of Fig. 15, the area of the convex portion at the top left represents the amount of charge required for hydrogen adsorption. Since the amount of charge used for hydrogen adsorption by platinum is fixed, the active area of the catalyst layer can be determined from the relative amount of charge. Referring to Fig. 15, it can be seen that the aforementioned area is widest in Example 2, followed by Example 1 and Comparative Example 1 which are nearly similar, and Comparative Example 4 which is the narrowest. This means that Example 2 has the best catalytic active area.
[0141] FIG. 16 is a graph comparing the power density according to the electrode area and Pt content of an electrode for a fuel cell manufactured according to one embodiment of the present invention.
[0142] Referring to FIG. 16, it can be inferred that high fuel cell efficiency can be achieved as Example 2 shows the highest power density and Example 1 shows the next highest power density.
[0143] FIG. 17 is an EIS curve of a fuel cell electrode manufactured according to one embodiment of the present invention.
[0144] Each semicircle in FIG. 17 represents the electron transfer resistance for the oxidation reaction of fuel at the fuel electrode. Referring to FIG. 17, it can be seen that the diameter of the semicircles increases in the order of Example 2, Example 1, Comparative Example 1, and Comparative Example 4. That is, it can be seen that the charge transfer resistance is smallest in Example 2 and largest in Comparative Example 4.
[0145] The above description is merely an illustrative explanation of the technical concept of the present invention, and those skilled in the art to which the present invention pertains will be able to make various modifications and variations within the scope of the essential characteristics of the present invention.
[0146] The fuel cell electrode of the present invention can reduce the amount of expensive Pt used, thereby allowing for the expectation of reduced manufacturing costs.
[0147] In addition, the electrode for a fuel cell of the present invention includes Pt-Ni composite particles as a catalyst layer, thereby enabling an improvement in catalyst efficiency due to the alloying effect.
[0148] In addition, the method for manufacturing an electrode for a fuel cell according to the present invention can reduce material costs and waste disposal costs by excluding the use of organic solvents and reducing agents, thereby allowing for the expectation of reduced manufacturing costs.
[0150] Accordingly, the embodiments disclosed in this invention are intended to illustrate, not limit, the technical concept of the invention, and the scope of the technical concept of the invention is not limited by these embodiments. The scope of protection of this invention shall be interpreted by the claims below, and all technical concepts within an equivalent scope shall be interpreted as being included within the scope of rights of this invention.
Claims
Claim 1 An electrode for a fuel cell comprising: a carbon support; and a catalyst layer comprising Pt-Ni composite particles formed on the surface of the carbon support. Claim 2 An electrode for a fuel cell according to claim 1, wherein the carbon support is one or more materials selected from the group consisting of carbon nanotubes. Claim 3 In claim 1, the carbon support is an electrode for a fuel cell having inherent structural defects. Claim 4 An electrode for a fuel cell according to claim 1, wherein the Pt-Ni composite particles are core-shell structured Pt-Ni composite particles or alloy-phase Pt-Ni composite particles. Claim 5 In claim 4, the Pt-Ni composite particles are an electrode for a fuel cell, wherein Pt and Ni are included in an elemental ratio of 1:1 to 6:
1. Claim 6 In claim 4, the core-shell structured Pt-Ni composite particle comprises Ni in the core and Pt in the shell, forming an electrode for a fuel cell. Claim 7 An electrode for a fuel cell according to claim 1, wherein the diameter of the Pt-Ni composite particle is 4 to 10 nm. Claim 8 In claim 1, the Pt loading amount of the electrode is 0.04 to 0.05 mg / cm² 2 Phosphorus, electrode for fuel cell. Claim 9 A method for manufacturing an electrode for a fuel cell, comprising the steps of: preparing a carbon support; and forming a catalyst layer containing Pt-Ni composite particles on the surface of the prepared carbon support. Claim 10 A method for manufacturing an electrode for a fuel cell, wherein the step of preparing the carbon support comprises: forming a carbon sheet through a carbon source; heat-treating the formed carbon sheet; and acid-treating the heat-treated carbon sheet. Claim 11 A method for manufacturing an electrode for a fuel cell according to claim 10, wherein the carbon source is one or more substances selected from the group consisting of ethanol, methanol, propanol, acetone, xylene, chloroform, ethyl acetic acid, diethyl ether, polyethylene glycol, ethyl formate, mesitylene, tetrahydrofuran (THF), dimethylformamide (DMF), dichloromethane, hexane, benzene, carbon tetrachloride, and pentane. Claim 12 A method for manufacturing an electrode for a fuel cell according to claim 10, wherein the thickness of the formed carbon sheet is 5 to 30 μm. Claim 13 A method for manufacturing an electrode for a fuel cell, wherein the step of forming the carbon sheet is performed according to a direct spinning method in claim 10. Claim 14 A method for manufacturing an electrode for a fuel cell according to claim 10, wherein the heat treatment is performed at a temperature of 450 to 650 ℃. Claim 15 A method for manufacturing an electrode for a fuel cell according to claim 10, wherein the acid treatment is performed using one or more acids selected from the group consisting of HCl, HNO3, HF, HClO4, H3PO4, HCrO4, and H2SO4. Claim 16 A method for manufacturing an electrode for a fuel cell, wherein the step of forming the catalyst layer is performed through a co-spurttering process using a Ni target and a Pt target on the surface of the prepared carbon support in claim 9. Claim 17 A method for manufacturing an electrode for a fuel cell according to claim 16, wherein the sputtering process is performed for 100 to 500 seconds. Claim 18 A method for manufacturing an electrode for a fuel cell, wherein the step of forming the catalyst layer in claim 16 is to sputter the Ni target or the Pt target individually, or to sputter the Ni target and the Pt target simultaneously. Claim 19 A polymer electrolyte fuel cell comprising: an electrode for a fuel cell comprising a carbon support and a catalyst layer comprising Pt-Ni nanoparticles formed on the surface of the carbon support; and a polymer ion exchange membrane.